Case Report: Efficacy of albumin dialysis for the reversal of bile cast nephropathy-induced acute kidney injury - Issac, Aaron G.; Yu, Michael A.; Rogers, Desiree M.; Subramanian, Ram M. (Frontiers in Nephrology, 2023)
Background Bile cast nephropathy (BCN) is an underdiagnosed renal complication associated with severe hyperbilirubinemia and is seen in patients with liver failure who have cholestatic complications. BCN-induced acute kidney injury (AKI) can require hemodialysis (HD), and the molecular adsorbent recirculating system (MARS) is a potentially useful therapeutic option. Case summary A 57-year-old male presented with jaundice persisting for 1 month, with laboratory test results indicative of hyperbilirubinemia and AKI. Abdominal imaging and a biopsy confirmed biliary ductal dilation secondary to a pancreatic head mass. The patient had rapidly progressive renal failure and refractory hyperbilirubinemia, despite biliary decompression, and was started on HD. Subsequent therapy with albumin dialysis therapy using MARS was successful in reversing the AKI, the cessation of HD, and the restoration of native renal function. Conclusion In the setting of BCN-induced AKI, timely initiation of MARS can provide a useful therapeutic strategy to reverse renal dysfunction and facilitate intrinsic renal recovery.